Diagnosing pulmonary arteriovenous malformations in the presence of atrial septal defect and anomalous pulmonary venous drainage—An imaging challenge. Issue 9 (5th August 2020) - Sasikumar, Deepa; Ayyappan, Anoop; Valakkada, Jineesh; Krishnamoorthy, Kavasseri Mahadevan
Abstract: Saline contrast echocardiography is a simple and effective method to diagnose the presence and type of right‐to‐left shunt in patients with unexplained cyanosis. It is considered a very sensitive test to diagnose pulmonary arteriovenous malformations. Our patient presented with unexplained cyanosis and transthoracic echocardiography showed an atrial septal defect and anomalous pulmonary venous drainage of the right and left upper pulmonary veins to the superior venacava. We describe how we used saline contrast echocardiography to demonstrate the presence of pulmonary arteriovenous malformations even in the presence of atrial septal defect and anomalous pulmonary venous drainage.